2004
DOI: 10.3406/paleo.2004.4770
|View full text |Cite
|
Sign up to set email alerts
|

Building houses, framing concepts, constructing worlds

Abstract: The thesis proposed here is that architecture exploded in the early Neolithic of southwest Asia as a novel and powerful system of symbolic representation, the scaffolding of a pre-literate mode of external symbolic storage. The ability to construct settlements, houses and public buildings that represented constructs of the world that they inhabited allowed new kinds of human society to evolve. By comparing the long Epipalaeolithic period and the trend towards sedentary village life with the rich architectural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 3 publications
0
30
0
Order By: Relevance
“…I have argued that the critical transformation from life in small-scale groups of fluid membership (a fissionfusion way of life that has roots deep in human evolution) to life in large-scale and permanent communities required cultural adjustments of an equally critical kind (Watkins, 2004a(Watkins, , 2004b(Watkins, , 2006(Watkins, , 2010(Watkins, , 2014. In company with a number of other archaeologists, biologists and evolutionary scientists, I believe that (cultural) niche construction theory allows us to articulate the nature of this transformation.…”
Section: Cultural Niche Construction Theory As a Framework For Undersmentioning
confidence: 98%
“…I have argued that the critical transformation from life in small-scale groups of fluid membership (a fissionfusion way of life that has roots deep in human evolution) to life in large-scale and permanent communities required cultural adjustments of an equally critical kind (Watkins, 2004a(Watkins, , 2004b(Watkins, , 2006(Watkins, , 2010(Watkins, , 2014. In company with a number of other archaeologists, biologists and evolutionary scientists, I believe that (cultural) niche construction theory allows us to articulate the nature of this transformation.…”
Section: Cultural Niche Construction Theory As a Framework For Undersmentioning
confidence: 98%
“…The agency of things is often considered in terms of how material culture contributed to the creation of social identities and manipulation of social relations (Sofaer Derevenski 2000, Bailey 2005), but things also mediated more fundamental relations between people and the world. Watkins (2004aWatkins ( , 2004bWatkins ( , 2010, for example, has argued that villages as a new form of built and cognitive environments contributed to, and indeed played a key role in, the broader economic, cultural and other developments associated with the Neolithic in south-west Asia. At the Neolithic transition, people began to use their built environment as a frame of symbolic reference, imbued with meaning and significance.…”
Section: The Neolithic Materials Culture and The Perception Of The Enmentioning
confidence: 98%
“…Natufian sites contain the traces of the first architectural constructions: typically round or oval pits reinforced with stones around their peripheries, some plastered with lime; remains of post holes that held beams to support a thatched roof are often found, as well as those of a hearth or two. A typical Natufian settlement comprised a cluster of such structures, and scholars of the Natufian culture agree (e.g., BarYosef (1998);Watkins (2004)) that these building groups were sedentary "hamlets" or at least the "base camps" of stable communities composed of 75-100 members that persisted over many years, often generations. This by itself points to a profound societal transformation: The typical size of a nomadic foragers' band, typically an extended family, is around 25, and only a handful of flimsy structures have been found that could be dated to pre-Natufian periods 3 .…”
Section: The Natufian Culture In the Levantmentioning
confidence: 99%